OPTIMALISASI PENGUSAHAAN LAHAN PETANI KELAPA SAWIT SWADAYA DI KABUPATEN TULANG BAWANG PROVINSI LAMPUNG - Sinaga, Shintia Maria Williyani; Ismono, Raden Hanung; Adawiyah, Rabiatul (Lampung University, 2018)
This research aimed (1) to analyze optimal income obtained by farmers with optimal use of labor and land both in mineral and in peat land, and (2) to identify palm oil marketing channel in Tulang Bawang District. The research was conducted by survey method in Penawar Tama and Gedung Aji Baru Subdistricts of Tulang Bawang District Lampung Province in July 2017. The sampling was done by census to 17 self-help palm oil farmers. Data were analyzed by using linear programming model, land productivity, farm income, and descriptive analysis of marketing channel. The results showed the optimal income that could be achieved in Scenario 1 was Rp32,805,860.00 with optimal labor usage of 120.28 HOK, whereas in Scenario 2 the optimal income that could be achieved was Rp46,976,300.00 with optimal labor usage for 125.2 HOK. There were 2 marketing channels of palm oil established in Kabupaten Tulang Bawang. Channel 1 with 76.47 percent of farmers started from the farmers, distributed to the wholesalers and then to palm oil mill. Channel 2 with 23.3 percent of farmers started from the farmers, distributed to the middlemen, to wholesalers and to palm oil mill. Key words: land optimalization, palm oil, marketing channel